A young lady with post-partum jaundice and right upper quadrant lump abdomen: an unusual etiology - Goswami, Amitava (Hellenic Society of Gastroenterology, 2014)
Intraductal papillary mucinious neoplasm-biliary type is the biliary counterpart of intraductal papillary mucinious neoplasm-pancreatic type. We report a rare case of intraductal papillary mucinous tumor arising from extrahepatic biliary system. The diagnosis was established on histopathological analysis following endoscopic retrograde cholangiopancreatography-guided biopsy. Isolated papillary adenoma of the bile duct is extremely rare, and in this unusual case the patient was a 22-year-old young lady who had delivered a healthy infant 6 weeks previously.